2012
DOI: 10.1039/c2ob06898b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photophysical evaluation of a pyridinium 4-amino-1,8-naphthalimide derivative that upon intercalation displays preference for AT-rich double-stranded DNA

Abstract: The synthesis, characterisation and solid state crystal structure of a cationic 4-amino-1,8-naphthalimide derivative (1) are described. The photophysical properties of 1 are shown to vary with the solvent polarity and H-bonding ability. The fluorescence of 1 is enhanced and blue-shifted in its 1 : 1 complex with 5′-adenosine-monophosphate while it is partially quenched and red-shifted in its complex with 5′-guanosine-monophosphate. Linear and circular dichroism measurements show that 1 binds to double-stranded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 68 publications
7
40
2
Order By: Relevance
“…1) with 5′-AMP, 5′-GMP and DNA, which showed that the compound exhibits an enhanced fluorescence emission in the presence of 5′-AMP and DNA, while the fluorescence is quenched by 5′-GMP, indicating that the singlet excited state of the 4-amino-1,8-naphthalimide derivative can oxidise guanine but not adenine. 10 This study also showed that in contrast to what was reported for the unsubstituted compound, 11 the 4-amino-derivative 1 binds to DNA via intercalation and displays a strong preference for AT-rich sequences. 10 To further probe the binding of 4-amino-1,8-naphthalimides with DNA, we have synthesised two novel structurally related derivatives 2 and 3 ( Fig.…”
Section: Introductioncontrasting
confidence: 43%
See 4 more Smart Citations
“…1) with 5′-AMP, 5′-GMP and DNA, which showed that the compound exhibits an enhanced fluorescence emission in the presence of 5′-AMP and DNA, while the fluorescence is quenched by 5′-GMP, indicating that the singlet excited state of the 4-amino-1,8-naphthalimide derivative can oxidise guanine but not adenine. 10 This study also showed that in contrast to what was reported for the unsubstituted compound, 11 the 4-amino-derivative 1 binds to DNA via intercalation and displays a strong preference for AT-rich sequences. 10 To further probe the binding of 4-amino-1,8-naphthalimides with DNA, we have synthesised two novel structurally related derivatives 2 and 3 ( Fig.…”
Section: Introductioncontrasting
confidence: 43%
“…10 This study also showed that in contrast to what was reported for the unsubstituted compound, 11 the 4-amino-derivative 1 binds to DNA via intercalation and displays a strong preference for AT-rich sequences. 10 To further probe the binding of 4-amino-1,8-naphthalimides with DNA, we have synthesised two novel structurally related derivatives 2 and 3 ( Fig. 1).…”
Section: Introductioncontrasting
confidence: 43%
See 3 more Smart Citations